Formal Education of Polish Society as a Factor Affecting Human Capital - Zdrojewski, Eugeniusz Z.; Toszewska-Czerniej, Weronika (Olsztyn Economic Journal, 2016)
Human resources in Poland have varied and valuable features and components that constitute significant human capital. A steady increase in the educational level of the society has a beneficial effect on the formation of capital. This study attempts to show the changes in the education of Polish society during the period of 1990-2014.